2020
DOI: 10.1002/pa.2315
|View full text |Cite
|
Sign up to set email alerts
|

A study of rice mill innovation for using in household that effects the marketing mix satisfaction of farmers in Thailand

Abstract: Thailand is a major rice grower and one of the top rice exporters in the world. Thailand's rice is recognized globally for its quality and is in high demand in a large number of countries. Milling is a crucial step in the post‐production of rice. The basic objective of a rice milling system is to remove the husk and the bran layers, to produce an edible, rice kernel that is free of impurities. This study focuses on the needs of the farmers to obtain the final product using rice mills as a household item with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The findings revealed that the marketing mix (varying products, price, place, and promotion) has a direct and significant impact on changeable consumer satisfaction. This study matched previous findings (Chen & Liu, 2019;Do & Vu, 2020;Sawmong, 2020). Based on past data, this study proposes that: Proposition 3: Promotion is positively related to the customer satisfaction.…”
Section: Promotion and Product Satisfactionsupporting
confidence: 88%
See 4 more Smart Citations
“…The findings revealed that the marketing mix (varying products, price, place, and promotion) has a direct and significant impact on changeable consumer satisfaction. This study matched previous findings (Chen & Liu, 2019;Do & Vu, 2020;Sawmong, 2020). Based on past data, this study proposes that: Proposition 3: Promotion is positively related to the customer satisfaction.…”
Section: Promotion and Product Satisfactionsupporting
confidence: 88%
“…According to the findings of this study, product quality has a considerable and beneficial impact on consumer satisfaction. This discovery is backed by a large number of other authors and researchers (e.g., Chen & Liu, 2019;Do & Vu, 2020;Sawmong, 2020). As a result, it is expected that the product will have an impact on consumer satisfaction in Malaysian gyms and fitness clubs.…”
Section: Product and Customer Satisfactionmentioning
confidence: 96%
See 3 more Smart Citations